'You just have to get through it': Letting go of enduring stereotypes about middle school. (October 2022) - Deutsch, Nancy L.
The prevailing cultural narrative about middle school is that those years are extremely difficult, and the best students can hope for is to endure them until finding relief in high school. Nancy Deutsch argues that these years are, in fact, a time of great potential if schools can abandon their stereotypes about young adolescents and create school cultures that build on their energy and willingness to explore new things. Deutsch discusses some common stereotypes about middle school and research findings that reveal the truth about the potential of students in the middle grades .